A framework for novelty detection in jet engine vibration data - Clifton, D; Bannister, P; Tarassenko, L (2007)
A novelty detection approach to condition monitoring of aerospace gas-turbine engines is presented, providing a consistent framework for on- and off-line analysis, each with differing typical implementation constraints. On-line techniques are introduced for observing abnormality in engine behaviour during aircraft flights, and are shown to provide early warning of engine events in real-time. Off-line techniques within the same analysis framework are shown to allow the tracking of single engines and fleets of engines from ground-based monitoring stations on a flight-by-flight basis. Results are validated by comparison to conventional techniques, in application to aerospace engines and other industrial high-integrity systems.